Measuring sloshing, merging, and feedback velocities in the Virgo cluster. Issue 3 (22nd September 2021) - Gatuzz, Efrain; Sanders, J S; Dennerl, K; Pinto, C; Fabian, A C; Tamura, T; Walker, S A; ZuHone, J
ABSTRACT: We present a detailed analysis of the velocity structure of the Virgo cluster using XMM–Newton observations. Using a novel technique which uses the Cu K α instrumental line to calibrate the EPIC-pn energy scale, we are able to obtain velocity measurements with uncertainties down to Δ v ∼ 100 km s −1 . We created 2D projected maps for the velocity, temperature, metallicity, density, pressure, and entropy with an spatial resolution of 0.25 arcmin. We have found that in the innermost gas there is a high velocity structure, most likely indicating the presence of an outflow from the AGN while our analysis of the cluster cool core using RGS data indicates that the velocity of the gas agrees with the M87 optical redshift. An overall gradient in the velocity is seen, with larger values as we move away from the cluster core. The hot gas located within the western radio flow is redshifted, moving with a velocity ∼331 km s −1 while the hot gas located within the eastern radio flow is blueshifted, with a velocity ∼258 km s −1, suggesting the presence of backflows. Our results reveal the effects of both AGN outflows and gas sloshing, in the complex velocity field of the Virgo cluster.